Tenkit ve Edebi Tenkit - Gülşen, Hacer (İstanbul Kültür Üniversitesi Yayınları, 2003)
Türk edebiyatına Batıdan gelmiş önemli bir tür olan tenkit, bizde Fransızca critique kelimesinin karşılığı olarak kullanılmıştır. Bazı sanatçılarımız, tenkit ile critique arasında bir ilgi olmadığını savunarak kelimeye başka şekillerde karşılıklar bulmuşlardır. Tenkidin bir çeşidi olan edebi tenkit ise, bir edebi eserin, ne dereceye kadar ve hangi sebeplerden ötürü iyi ya da kötü olduğuna karar verme sanatı olarak önem taşımaktadır. Criticism in Turkish Literature or the Turkish term for it in Turkish Literature: "tenkit", iöported from the West, has been introduced into our language via the french word "critique". Some of our artists who claimed that there is no relationship between "tenkit" and "critique" have found other equivalents for this term. Literary criticism, another kind of criticism, plays an important role in the decision making about a literary work, i.e. it determines the aspects of its success or failure and the reasons why it is labelled good or bad.
Keywords: Tenkit; Criticism; Kritik; Critique; Edebi; Literary